2023
DOI: 10.1177/20552076231182805
|View full text |Cite
|
Sign up to set email alerts
|

Using the TIDieR checklist to describe development and integration of a web-based intervention promoting healthy eating and regular exercise among older cancer survivors

Abstract: Objective To facilitate replication and future intervention design of web-based multibehavior lifestyle interventions, we describe the rationale, development, and content of the Ai M, Plan, and act on LIFest Yles (AMPLIFY) Survivor Health intervention which provides healthy eating and exercise behavior change support for older cancer survivors. The intervention promotes weight loss, improvements in diet quality, and meeting exercise recommendations. Methods The Template for Intervention Description and Replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…AMPLIFY adaptation process was conducted in three phases spanning six years: (1) formative assessment and intervention development; (2) beta-testing and refinement; and (3) efficacy testing and process evaluation (Rogers et al, 2023). Multiple forms of quantitative and qualitative data were collected, analyzed, and integrated using concurrent and sequential timing to inform the adaptation processes in all phases, thus forming a complex (Creswell & Plano Clark, 2018) or scaffolded (Fetters, 2020) longitudinal mixed methods design intersected with an overall AM-PLIFY intervention design (Plano Clark & Ivankova, 2016) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…AMPLIFY adaptation process was conducted in three phases spanning six years: (1) formative assessment and intervention development; (2) beta-testing and refinement; and (3) efficacy testing and process evaluation (Rogers et al, 2023). Multiple forms of quantitative and qualitative data were collected, analyzed, and integrated using concurrent and sequential timing to inform the adaptation processes in all phases, thus forming a complex (Creswell & Plano Clark, 2018) or scaffolded (Fetters, 2020) longitudinal mixed methods design intersected with an overall AM-PLIFY intervention design (Plano Clark & Ivankova, 2016) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…AMPLIFY was developed by adapting traditional modalities (i.e., face-to-face and print materials) of two previously tested diet and exercise interventions BEAT Cancer and RENEW (Morey et al, 2009;Rogers et al, 2015) both of which were found efficacious, to a web-based delivery. This work was performed under a program grant funded by the National Cancer Institute in 2018 (P01CA229997; Pekmezi et al, 2022;Rogers et al, 2023). AMPLIFY provides healthy eating and exercise behavior change support to promote weight loss, improvements in diet quality, and adherence to physical activity.…”
Section: Amplify Interventionmentioning
confidence: 99%
See 3 more Smart Citations